2021
DOI: 10.1177/17480485211029021
|View full text |Cite
|
Sign up to set email alerts
|

Differences in journalism culture or is there more to it? Comparing news on the European refugee issue in Western Europe and China

Abstract: This study explores the country-specific, regional and cultural differences and similarities between China and two European countries in their coverage of the European refugee issue and seeks to provide a deeper understanding of the various political interests, social values, and journalism cultures in the countries under study. It analyzed and compared 2,368 news articles in Belgian, Swedish, and Chinese newspapers from 2015 to 2017. The analysis demonstrated that Chinese newspapers put less emphasis on welco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The cultivation of journalism culture is often intertwined with specific political and media systems (Jiang et al, 2021). The global expansion of media industries, primarily from advanced capitalist countries, notably the United States, has contributed to greater uniformity in media systems and journalism practices (Hallin & Mancini, 2004).…”
Section: Transnational Heterogeneity Of Network Agendamentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivation of journalism culture is often intertwined with specific political and media systems (Jiang et al, 2021). The global expansion of media industries, primarily from advanced capitalist countries, notably the United States, has contributed to greater uniformity in media systems and journalism practices (Hallin & Mancini, 2004).…”
Section: Transnational Heterogeneity Of Network Agendamentioning
confidence: 99%
“…The ethical ideologies point to how journalists respond to ethical dilemmas. Previous comparative studies indicated journalists sharing similar professional beliefs and practices tend to construct comparable media agenda, news framing and news sourcing (Jiang et al, 2021). The reason could be that journalists who are amid comparable news culture tend to adhere to similar journalistic norms and values, undergo analogous media education and training, and work in industries with similar ownership structures and political proximity.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Hepp et al (2012) argue that news media are situated in distinct discourse cultures, which are integral for the formation of (national) public spheres. Language, the dominant political system and its ideological foundation, the structure of the media system and level of access to media technology, the legal framework and prevailing cultural norms give discourse cultures their forms (Jiang, d'Haenens, & Zhang, 2021;Hanitzsch, 2009). Discourse cultures differ along linguistic-cultural and political lines (e.g.…”
Section: News Framing the Localisation Of Global Trends And Discourse...mentioning
confidence: 99%
“…Chouliaraki and Zaborowski, 2017;Sakellari, 2021;Vollmer and Karakayali, 2018), newspapers and websites (e.g. Cooper et al, 2021;Fengler et al, 2020;Greussing and Boomgaarden, 2017;Jiang et al, 2021;Tong and Zuo, 2019;Zaman and Das, 2021), and social media sites and user-generated content (e.g. Abid et al, 2017;Bennett, 2018;Creta, 2021).…”
Section: Introductionmentioning
confidence: 99%